GULF REGION STUDENTS’ COPING STRATEGIES OF THEIR CULTURAL CHALLENGES AT U.S. UNIVERSITIES - Al Murshidi, Ghadah (European Scientific Journal, ESJ, 2014)
The present study examines social and cultural challenges Emirati and Saudi students face at U.S. universities, and investigates Emirati and Saudi students' coping strategies to face their challenges. Based on a sample of 219, a mixed methods approach was used to analyze responses from participants who responded to a questionnaire that had been posted online (Qualtrics). The results of the questionnaire instrument reveal that Emirati students are more comfortable than Saudi students in working with a different gender in their classes. Also, the survey shows that Emirati and Saudi students felt comfortable in discussing cultural issues related to their regions in class. However, the interviews results indicate that Saudi male student tried to adjust to the challenges of American culture, which requires independence and completing household chores. Emirati and Saudi female students face communication challenges with male classmates. Giving Saudi female students more freedom to deal with personal life in the U.S. is different than their country-of-origins' traditions. Having parents accompany female students during the first experience in the U.S. helps accommodation. Also, having dependents with female students smoothen their transitions. Further analysis used in-depth interviews to expand the analysis of the lived experiences from six participants 'interviews. Some categories that are produced from the data are related to cultural adjustment and gender issues. In general, results show more similarities between Emirati and Saudi students because UAE and Saudi Arabia are global countries and have strong connection with U.S., and have similar history of education system reform.